Heavy metal concentration in sediment of Sarawak seawater - Noor Fazreen, D.; Noor Azmi, Azran Azhim (2014)
This study was conducted to investigates the correlation of heavy metal and its physico-chemical characteristics in the sediment of Sarawak seawater. The statistical analysis were performed and the correlation of heavy metals concentration and the physico-chemical characteristic were determined. The results show the heavy metal concentration at all sampling stations occurs in descending order of Vanadium > Barium > Zinc > Nickel > Chromium. Correlation analysis of the data showed that salinity and Total Organic Carbon (TOC) have significant correlation with the heavy metal concentration.